2023
DOI: 10.1021/acs.jchemed.3c00452
|View full text |Cite
|
Sign up to set email alerts
|

Investigating How Chemistry Students’ Reported Challenges Inform the Relationship between Mindset and Academic Performance

Betül Demirdöğen,
Scott E. Lewis

Abstract: Mindset theory describes a context-dependent belief system on the degree that intelligence can change with effort. Students' chemistry mindsets may predict students' behavioral responses to challenges they experience within a chemistry course. This study was designed to investigate whether challenges mediate the relationship between chemistry mindset and academic performance. 745 first-semester general chemistry students participated in the study. The students were surveyed on their mindset at the beginning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…How mindset relates to self-efficacy and goal orientation has been found to depend on setbacks or challenges that students face throughout the term. , Additionally, struggling through a course may lead to a shift toward fixed mindset beliefs and students who reported challenges related to chemistry ability in general and organic chemistry courses were found to be more likely to hold a fixed mindset and have lower performance outcomes than students who reported other challenges . A recent study found that the relation between students’ chemistry mindset and summative achievement was completely mediated through chemistry-related challenges . Therefore, exploring students’ mindset and academic achievement throughout the term may provide valuable information about a potential relation between failing or succeeding in a course and students’ mindset throughout.…”
Section: Implications For Researchmentioning
confidence: 99%
“…How mindset relates to self-efficacy and goal orientation has been found to depend on setbacks or challenges that students face throughout the term. , Additionally, struggling through a course may lead to a shift toward fixed mindset beliefs and students who reported challenges related to chemistry ability in general and organic chemistry courses were found to be more likely to hold a fixed mindset and have lower performance outcomes than students who reported other challenges . A recent study found that the relation between students’ chemistry mindset and summative achievement was completely mediated through chemistry-related challenges . Therefore, exploring students’ mindset and academic achievement throughout the term may provide valuable information about a potential relation between failing or succeeding in a course and students’ mindset throughout.…”
Section: Implications For Researchmentioning
confidence: 99%
“…It is imperative to note the emphasis on the student’s interpretations ; a quick heartbeat during an exam can be interpreted as (1) excitement toward finishing a unit and receiving a good grade or (2) anxiety toward test performance and receiving a poor grade. Similarly, an optimistic outlook can allow students to reframe setbacks as opportunities for growth, as opposed to failures. , Course instructors and peer instructors can create a low-stress environment to take advantage of this effect; for instance, high-stakes exams can be minimized and teaching practices such as cold-calling can be avoided . Additionally, peer instructors can share personal stories of overcoming various course-related challenges, helping students believe they can do the same.…”
Section: Step Back Translate and Extend: Sources Of Self-efficacymentioning
confidence: 99%